Education supply chain management model to achieve sustainability in private Universities in Malaysia: a review - Basu, Govindaraju; Jeyasingam, John; Habib, Md Mamun (© 2016 ExcelingTech Pub., 2018)
This article was published in the International Journal of Supply Chain Management [ © 2016 ExcelingTech Pub, UK. ]